Answer:
ubeovgtnwjggswgtepibvqyytkhfhduygvtqyaccjvgvdbbetedgtdgyegghjgdbecdkbfbgdhebhjegeckgbkhbeiubuvvsakvhfe
Step-by-step explanation:
hrtrrrrrrrrrrrrrrrrhhhhhhrhhhhhhhhhhhhhhhhhhhhhhhhhhhhrhhrhhrrhhhrhhhhh
Answer:a
Step-by-step explanation:
Answer:
j=1
Step-by-step explanation:
Answer:
I can't even find the rational expression
Step-by-step explanation:
Did you forget something?
Answer:
-3
Step-by-step explanation:
Step 1: Solve (-2+(-1))^2/3 3
1. -2+(-1) = -3
2. (-3)^2 = 9
3. 9/3 = 3
Step 2: Solve (-4)^2-17 -1
1. 3/-1
Step 3: Simplify 3/-1 = -3. I hope this helped and please don't hesitate to reach out with more questions!